Measuring Residential Energy Efficiency Improvements with DEA - Peter Grösche (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2008)
This paper measures energy efficiency improvements of US single-family homes between 1997 and 2001 using a two-stage procedure. In the first stage, an indicator of energy efficiency is derived by means of Data Envelopment Analysis (DEA), and the analogy between the DEA estimator and traditional measures of energy efficiency is demonstrated. The second stage employs a bootstrapped truncated regression technique to decompose the variation in the obtained efficiency estimates into a climatic component and factors attributed to efficiency improvements. Results indicate a small but significant improvement of energy efficiency over the studied time interval, mainly accounted for by fuel oil and natural gas users.
Keywords: C14; C61; D13; Q4; 330; Energy efficiency; household production; data envelopment analysis; bootstrap; Energiesparen; Energiesparendes Bauen; Privater Haushalt; Technische Effizienz; Data-Envelopment-Analyse; USA